Conversion of Ligno-cellulosic Biomass Waste into Cellulose Nano-Fibril (CNF) Biodegradable Film for Bioactive Food Packaging - Ratna Dewi Kusumanintyas (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Indonesia is rich in tropical fruit. However, many tropical fruits face a post-harvesting problem related to the short shelf-life of fruits due to the high respiration, transpiration, and decaying by fungi. To solve this problem, it is necessary to prolong the shelf-life of tropical fruit by applying bioactive food packaging which can prevent fruit from decaying and rotting. Among the prospective bioactive food packaging is biodegradable film made of cellulose nanofibril (CNF). CNF is new nanomaterial containing thin fiber from cellulose. This material forms transparent gel, thus it is easily to be modified into biodegradable film which is homogenous, safe, environmentally friendly, and renewable. CNF nanomaterial can be derived from lingo-cellulosic material through the process of lingo-cellullose degradation followed by homogenization using fluidization process. This process results in CNF transparent gel which can be readily modified as biodegradable film. This biodegradable film is then can be applied to the tropical fruits to prolong their shelf-life. CNF bioactive food packaging has high mechanical strength and high protection against oxidation process. This paper comprehensively reviews the advanced technology of upgrading lingo-cellulosic biomass waste into CNF biodegradable film and the technic of applying it as bioactive fruit packaging.